Application of the Retroactive Principle in Criminal Law on Gross Human Rights Violations - Joko Sasmito (APPTHI, 2017)
AbstractStarting from the development of law in Indonesia to resolve the problem of gross human rights violations, it is necessary to establish a human rights court that is specifically a court for gross human rights violators. The superiority of regulating human rights in the constitution provides a very tight guarantee because amendments and/or deletion of one of the articles in the constitution, such as in the Indonesian constitution, experience a very difficult and lengthy process, while the weakness is that what is regulated in the constitution only contains rules that are still global in nature. The purpose of this research is to find out and understand the existence of the principle of legality in the applicable laws and regulations in Indonesia, restorative policies in law enforcement against human rights violations in the legal context in Indonesia, and find the ideal legal concept in law enforcement against human rights violations. The type of research to be used is included in the normative legal research group, namely legal research on legal principles, legal systematics, legal synchronization, comparative law, and legal history. So, research or study of legal norms is the legal system’s contents. The results of the study found that the legality principle in Indonesian laws and regulations still needs to be maintained because the essence of the legality principle is to create legal certainty and justice. Retroactive policies in law enforcement against human rights violations in the context of Indonesian law need to be carried out to uphold justice because there are general or greater benefits than protecting the rights of perpetrators that are partial. The ideal concept in retroactive policies against gross human rights violations is to clarify the substance of statutory provisions regarding retroactive enforcement of extraordinary crimes Abstrak Berawal dari perkembangan hukum di Indonesia untuk menyelesaikan masalah pelanggaran HAM berat, maka perlu dibentuk pengadilan HAM yang khusus merupakan pengadilan bagi pelanggar HAM berat. Keunggulan pengaturan hak asasi manusia dalam konstitusi memberikan jaminan yang sangat ketat karena perubahan dan/atau penghapusan salah satu pasal dalam konstitusi, seperti dalam konstitusi Indonesia, mengalami proses yang sangat sulit dan panjang, sedangkan kelemahannya adalah yang diatur dalam konstitusi hanya memuat aturan-aturan yang masih bersifat global. Tujuan penelitian ini adalah untuk mengetahui dan memahami adanya asas legalitas dalam peraturan perundang-undangan yang berlaku di Indonesia, kebijakan restoratif dalam penegakan hukum terhadap pelanggaran HAM dalam konteks hukum di Indonesia, dan menemukan konsep hukum yang ideal dalam penegakan hukum terhadap pelanggaran HAM. Jenis penelitian yang akan digunakan termasuk dalam kelompok penelitian hukum normatif yaitu penelitian hukum tentang asas-asas hukum, sistematika hukum, sinkronisasi hukum, perbandingan hukum dan sejarah hukum. Jadi, penelitian atau penelaahan terhadap norma hukum yang merupakan isi dari sistem hukum. Hasil kajian menemukan bahwa asas legalitas dalam peraturan perundang-undangan di Indonesia masih perlu dipertahankan keberadaannya, karena hakikat asas legalitas adalah untuk menciptakan kepastian dan keadilan hukum. Kebijakan retroaktif dalam penegakan hukum terhadap pelanggaran HAM dalam konteks hukum Indonesia perlu dilakukan untuk menegakkan keadilan karena ada kemanfaatan yang bersifat umum atau lebih besar dari perlindungan hak pelaku yang bersifat parsial. Konsep ideal dalam kebijakan retroaktif terhadap pelanggaran HAM berat adalah memperjelas substansi ketentuan perundang-undangan tentang pemberlakuan retroaktif terhadap kejahatan luar biasa. Kata kunci: Asas Retroaktif, Hukum, Hukum Pidana, Hak Asasi Manusia, Pelanggaran Hak Asasi Manusia